2020
DOI: 10.1155/2020/8186106
|View full text |Cite
|
Sign up to set email alerts
|

P2X3 Receptor in Primary Afferent Neurons Mediates the Relief of Visceral Hypersensitivity by Electroacupuncture in an Irritable Bowel Syndrome Rat Model

Abstract: Background. Electroacupuncture (EA) has been confirmed effectiveness in the treatment of irritable bowel syndrome (IBS), and P2X3 receptors in the peripheral and central neurons participate in the acupuncture-mediated relief of the visceral pain in IBS. Objective. To reveal the neurobiological mechanism that P2X3 receptor of colonic primary sensory neurons in the dorsal root ganglia of the lumbosacral segment is involved in the alleviation of visceral hypersensitivity by EA in an IBS rat model. Methods. The IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The analgesic effect of EA on visceral hypersensitivity has been extensively demonstrated (40)(41)(42)(43)(44), and the results of our study are consistent with this. EA reduced AWR scores and increased PWT, indicating that EA attenuated the visceral sensitization and peripheral mechanical hyperalgesia of PI-IBS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The analgesic effect of EA on visceral hypersensitivity has been extensively demonstrated (40)(41)(42)(43)(44), and the results of our study are consistent with this. EA reduced AWR scores and increased PWT, indicating that EA attenuated the visceral sensitization and peripheral mechanical hyperalgesia of PI-IBS.…”
Section: Discussionsupporting
confidence: 91%
“…Sensitization of visceral DRG neurons could contribute to triggering visceral hypersensitivity ( 49 ). It is reported that DRG plays an important role in the regulation of visceral hypersensitivity in IBS by EA ( 41 , 50 , 51 ). EA treatment can significantly inhibit the enhanced excitability of colon DRG neurons and reduce the peripheral sensitization status ( 41 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture, a traditional Chinese medicine therapy, has been extensively used for the treatment of gastrointestinal disorders, and it may also be a promising complementary and alternative therapy for IBS ( Manheimer et al, 2012 ; Guo et al, 2020 ; Zhang et al, 2020 ; Chen Y. et al, 2021 ). A series of clinical studies have shown that acupuncture can alleviate IBS-related symptoms, including abdominal pain, abdominal distension, bowel movement, scores for anxiety, depression, and sleep quality ( Li et al, 2017 ; Pei et al, 2020 ; Guo et al, 2021 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that EA could regulate the expression of the P2X3 receptors in the peripheral and central pathways of visceral pain transmission to achieve remission of VH in the IBS rat model ( Weng et al, 2015 ). EA downregulated the increased expression of P2X3 receptors in the colonic myenteric plexus and colon-associated dorsal root ganglion (DRG) neurons and is involved in the attenuation of VH in rats with the IBS model ( Zhang et al, 2020 ). EA can attenuate VH in the IBS rat model by decreasing the expression of P2X4 receptors in the colon ( Guo et al, 2013 ).…”
Section: Peripheral Mechanism Of Electro-acupuncture For Reducing Visceral Hypersensitivitymentioning
confidence: 99%
“…Past studies have shown the relief of pain in response to acupuncture therapy as compared with the sham acupuncture or control groups. Acupuncture treatment is being associated with the change in the concentrations of β-endorphin, epinephrine, and serotonin and the levels of c-Fos, substance P, cytokines, P2X3, acetylcholine (Ach), N -methyl- D -aspartate (NMDA) receptors, and serotonin in the gut/spinal cord ( Wan et al, 2017 ; Lee et al, 2019 ; Tan et al, 2019 ; Zhang et al, 2020 ). These studies show that electro-acupuncture (EA) can be used as an effective therapy to relieve VH.…”
Section: Introductionmentioning
confidence: 99%